Partogram: clinical study to assess the role of Partogram in primigravidae in labor - VR, Manjulatha; GS, Anitha; Shivalingaiah, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Good obstetrician must always be alert to detect any sign and symptoms of abnormal labor. Prolongation of labor presents a picture of mental anguish, physical morbidity and may lead to surgical intervention. The goal of this study is to use partograph to monitor labor, initiate uterine activity that is sufficient to produce cervical change and fetal descent while avoiding uterine hyperstimulation, hypostimulation and fetal distress and provide timely surgical intervention where required. Methods: Total of 100 primigravidae, who were booked with us till term were selected for the study and partograph recordings were commenced at 4 cm dilatation. Close foetal and maternal monitoring was done throughout the labour and Partogram was plotted to detect any deviation from normal course. Results: Based on the Partogram findings the patients were grouped into “before alert line” and “between alert and action line” the mode of delivery in these patients was studied. Of the 42% of women who came into this group, 52.3% underwent cesarean delivery, 42.5% had instrumental deliveries and the remaining had vaginal deliveries. Conclusions: This study shows that using the Partogram improves the quality of delivery care, since it permits to identify dystocia and make logical and effective interventions. It reduces unnecessary strain on mothers by reducing total duration of labour, without any increased foetal morbidity and mortality. If accepted as routine procedure, it will be suitable in all situations where the labour room remains busy and congested day and night for better and more efficient management of labour.